The Southeast Asian Animation Industry: Growing up under the Shadow of Neoliberalism - Windarti, Ani (Curtin University, 2021)
This thesis discusses the ways in which the animation industries in four Southeast Asian countries: Singapore, Malaysia, the Philippines and Indonesia, have countered the domination of Western and Japanese animation from a political economy perspective. It examines the effects of neoliberalism and national cultural policies on the organisation and works of the animation industry in Southeast Asia through an analysis of the New International Division of Cultural Labour (NICL).